Negotiating time and space on a study abroad program in South India. Issue 1 (2nd January 2016) - Hangen, Susan; Sen, Ruma
Abstract : This paper investigates the context of student learning in study abroad programs, drawing on ethnographic research on a semester long study abroad program in South India. We show how students use multiple constructions of time and space as a framework for understanding cultural differences and for understanding what it means for them to "experience" India. We argue that students' conceptualization of space and time in the study abroad location also impacts what kinds of activities they consider to count as valuable forms of learning. Students' ideas about India shape their expectations of what the pace, workload, and activities of the study abroad program in India should entail. Their concepts of Indian time and space lead them to privilege "experience"-based learning over classroom-based or scholarship-based learning. In conclusion, we show how these insights have implications for study abroad pedagogy. Here, we suggest that student learning that is entirely based on "experience" outside the classroom is inherently limited and that students need to contextualize their field-based learning experiences with insights from critical, historical and social science research.